Pemilihan Wisudawan Terbaik Menggunakan Sistem Pendukung Keputusan dengan Metode Profile Matching - Ermawati, Yuli; Zulkarnain, Zulkarnain; Majalista, Riya (Indo-MathEdu Intellectuals Journal, 2024)
The selection of the best graduate is an important process in the graduation ceremony to recognize students who have demonstrated outstanding academic and non-academic achievements during their studies. However, this process often faces challenges, particularly regarding the subjectivity and complexity of assessment. Therefore, a Decision Support System (DSS) is needed to assist in determining the best graduate objectively and transparently. The criteria used include academic achievements (GPA), involvement in organizational activities, non-academic achievements, attendance, and social contributions. Each criterion is weighted according to its level of importance. With the implementation of this DSS, it is hoped that the selection of the best graduate can be conducted more effectively, efficiently, and fairly. Testing results show that this system can provide accurate results that meet stakeholder expectations.